2018
DOI: 10.1111/eea.12681
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of plant cytokinin levels in the Wolbachia‐free leaf‐mining species Phyllonorycter mespilella

Abstract: As phytohormones lie at the very core of molecular mechanisms controlling the plant physiology and development, they have long been hypothesized to be involved in insect-induced plant manipulations. Cytokinins (CKs) are phytohormones now widely recognized to be utilized by leaf-mining and gall-inducing insects in the control of the physiology of their host plant. In some leaf-mining moth species, larvae can supply the hormones themselves, bacterial symbionts contributing to the production of CKs. Our objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The detailed analyses of movement and source of CKs participated in plant feeding by leaf-mining insects has revealed that the insect symbiotic bacteria Wolbachia is inherently involved . This complicated plant-insect-microbe interaction is essential and the modulation of plant CK levels was shown to be impaired in the Wolbachia-free leaf feeding moth (Zhang et al, 2018).…”
Section: Role Of Cytokinin For Interaction Of Plants With Pest Insectsmentioning
confidence: 99%
“…The detailed analyses of movement and source of CKs participated in plant feeding by leaf-mining insects has revealed that the insect symbiotic bacteria Wolbachia is inherently involved . This complicated plant-insect-microbe interaction is essential and the modulation of plant CK levels was shown to be impaired in the Wolbachia-free leaf feeding moth (Zhang et al, 2018).…”
Section: Role Of Cytokinin For Interaction Of Plants With Pest Insectsmentioning
confidence: 99%
“…By covering gall, we mean the plant tissue that envelopes the gall-inducing organism. Among fungi and insects that encounter senescing plant tissues, some species appear to employ CKs to induce yellowing plant tissues to "stay green" by the process of forming "green islands"-areas of photosynthetically active tissues in which the pathogenic organism can continue to feed and develop [17,[51][52][53][54][55][56][57]. In some instances, CKs have been shown to convert the site of attack into a mobilizing sink to which sugars are translocated where they may contribute to gall induction or just for the sustenance of the manipulating organism [18,28,45,[58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The earliest studies used bioassays to confirm the presence of CKs in insects [66][67][68][69][70]. Since then, researchers have used either ELISA [52,54,55], or analytical chemistry [15][16][17]19,44,46,47,49,50,57], to estimate the concentrations of CKs in insects.…”
Section: Introductionmentioning
confidence: 99%
“…CKs also accumulate to high levels in mined tissues, despite low levels of plant CK-related gene expression. Very large amounts of CKs have also been found in many leaf-mining insects, including the leaf-mining moths Phyllonorycter mespilella and Phyllonorycter blancardella (Lepidoptera), and the production of these hormones by the insect may be linked to the presence of bacterial endosymbionts (75,144,146).…”
Section: Recognition Of Plant-reprogramming Parasites and Defense Supmentioning
confidence: 99%